2010
DOI: 10.1113/jphysiol.2009.184580
|View full text |Cite
|
Sign up to set email alerts
|

Increased vasopressin transmission from the paraventricular nucleus to the rostral medulla augments cardiorespiratory outflow in chronic intermittent hypoxia-conditioned rats

Abstract: A co-morbidity of sleep apnoea is hypertension associated with elevated sympathetic nerve activity (SNA) which may result from conditioning to chronic intermittent hypoxia (CIH). Our hypothesis is that SNA depends on input to the rostral ventrolateral medulla (RVLM) from neurons in the paraventricular nucleus (PVN) that release arginine vasopressin (AVP) and specifically, that increased SNA evoked by CIH depends on this excitatory input. In two sets of neuroanatomical experiments, we determined if AVP neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
94
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 92 publications
3
94
0
1
Order By: Relevance
“…Not only do MnPO neurons heavily innervate the downstream hypothalamic PVN (39,58,59), but virus-mediated expression of a mutant JunD construct that interferes with FosB/⌬FosB transcriptional regulation in MnPO neurons largely prevents the sustained hypertension during normoxia resulting from 7 days of CIH (8). The latter is consistent with results from previous reports (7,9,25,27,53) and of the present study, which indicate that CIH tonically actives the downstream PVN.…”
Section: Discussionsupporting
confidence: 82%
“…Not only do MnPO neurons heavily innervate the downstream hypothalamic PVN (39,58,59), but virus-mediated expression of a mutant JunD construct that interferes with FosB/⌬FosB transcriptional regulation in MnPO neurons largely prevents the sustained hypertension during normoxia resulting from 7 days of CIH (8). The latter is consistent with results from previous reports (7,9,25,27,53) and of the present study, which indicate that CIH tonically actives the downstream PVN.…”
Section: Discussionsupporting
confidence: 82%
“…41 At the central nervous system level, important alterations in mechanisms of neurotransmission in neuronal groups critically involved with the processing of sympathetic chemoreflex response, such as in the nucleus tractus solitarius, 42,43 the hypothalamus, 44,45 and the ventral medulla, have been reported. [46][47][48] These peripheral and central alterations of chemoreflex pathways induced by CIH contribute to the facilitation of sympathetic chemoreflex response, and it represents an important mechanism of long-lasting excitation of medullary presympathetic neurons in response to new episodes of hypoxia and sustained increase of baseline sympathetic outflow after CIH.…”
Section: Mechanisms Involved In the Generation Of Sympathetic Overactmentioning
confidence: 99%
“…There is evidence of plastic changes in peripheral (50) and central (16,27,32,35,60) components of chemosensory control of sympathetic and respiratory activities. The latter includes changes in the interaction between sympathetic and respiratory neuronal populations (1,59) and alterations in neurochemical mechanisms in important brain stem areas (30,31). Previous in vitro studies reported that glutamatergic signaling is altered in the NTS of rats submitted to CIH (20,32).…”
Section: Discussionmentioning
confidence: 99%